Nanostructured, Self-Assembling Peptide K5 Blocks TNF-α and PGE2 Production by Suppression of the AP-1/p38 Pathway - Woo Seok Yang; Yung Chul Park; Ji Hye Kim; Hye Ri Kim; Tao Yu; Se Eun Byeon; Larry D. Unsworth; Jaehwi Lee; Jae Youl Cho (Mediators of Inflammation)
Nanostructured, self-assembling peptides hold promise for a variety of regenerative medical applications such as 3D cell culture systems, accelerated wound healing, and nerve repair. The aim of this study was to determine whether the self-assembling peptide K5 can be applied as a carrier of anti-inflammatory drugs. First, we examined whether the K5 self-assembling peptide itself can modulate various cellular inflammatory responses. We found that peptide K5 significantly suppressed the release of tumor-necrosis-factor- (TNF-) α and prostaglandin E2 (PGE2) from RAW264.7 cells and peritoneal macrophages stimulated by lipopolysaccharide (LPS). Similarly, there was inhibition of cyclooxygenase- (COX-) 2 mRNA expression assessed by real-time PCR, indicating that the inhibition is at the transcriptional level. In agreement with this finding, peptide K5 suppressed the translocation of the transcription factors activator protein (AP-1) and c-Jun and inhibited upstream inflammatory effectors including mitogen activated protein kinase (MAPK), p38, and mitogen-activated protein kinase kinase 3/6 (MKK 3/6). Whether this peptide exerts its effects via a transmembrane or cytoplasmic receptor is not clear. However, our data strongly suggest that the nanostructured, self-assembling peptide K5 may possess significant anti-inflammatory activity via suppression of the p38/AP-1 pathway.